Vigas, R. The convent of Santa Monica in the religious territory of the Augustinians in Monte Santo de Goa (17th century) - Oliveira, Rozely Menezes Vigas (2024)
The Congregação dos Eremitas de Santo Agostinho da Índia Oriental played a very important role in the spread of the Catholic faith in Asia. Despite his late arrival to the East, in 1572, his missionary action reached China, working mainly in Hormuz and Persia, with an important shipment of religious. The missionaries who would work on these missions, whether they came from the kingdom or professed in Portuguese Asia, set out from the city of Goa. The Convent of Nossa Senhora da Graça, in Goa, became the mother house of the congregation from its early years, while Monte Santo became an almost exclusively Augustinian territory, concentrating five Augustinian houses and churches, among them the Convent from Santa Monica. To reflect on the feeling of belonging of the female monastery to the congregation and of both to Monte Santo, this paper proposes a brief analysis of the stories present in the Augustinian chronicles about their performance in the East, through the concept of religious territoriality. Thus, it will be possible to understand how the summit of Monte Santo was transformed into a predominantly Augustinian territory and how religious men and women appropriated and identified with it.